Pengembangan Bahan Ajar Berbasis Kontekstual untuk Meningkatkan Pemahaman Siswa - Febriani Paudi; Oktavia Ngaito (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Contextual Teaching and Learning (CTL) is a pedagogical approach that links the learning material to students' everyday life, making the learning process more meaningful and easier to understand. The aim of this literature review is to identify the effectiveness of context-based teaching materials in enhancing students' conceptual understanding, motivation, and learning outcomes in elementary schools. Studies focusing on the development of teaching materials, interactive modules, contextual worksheets, and e-modules were analyzed in depth. The findings show that the contextual approach consistently enhances student engagement, conceptual understanding, and critical thinking skills. However, several challenges need to be addressed, such as limited resources, lack of teacher competence, and the scarcity of relevant local learning resources. This article provides strategic recommendations related to the development and implementation of more effective and sustainable context-based teaching materials, taking into account resource availability and the improvement of teacher competencies to ensure the success of contextual learning in elementary schools.